Au Grade of Epithermal Gold Ore at Paningkaban ASGM, Banyumas District, Central Java Province, Indonesia - Rika Ernawati; Arifudin Idrus; HTBM Petrus (UPT Penerbitan Universitas Jember, 2016)
There are many Artisanal Small scales Gold Mine (ASGM) in Indonesia, one of them is epithermal gold ore at Paningkaban, Banyumas District, Central Java Province. The activity has been for about twenty years. The existence of ASGM at Paningkaban still takes place until now. It can be an indicator that they are still many gold resources. The aim of the research is the analysis of Au grade and other metal, such as Cu, Ag, Pb, As, Zn and Hg. The research methods are literature study from previous research, field work, laboratory work, and interpretation. The literature study comes from previous research at the location. The field work comprised direct observation and taking the sample of gold ore/vein in the location of research. Fieldwork is done for a week to obtain gold ore/ vein. The sixteenth samples were analyzed to obtain ore/metal grades. The fifth of the highest Au grade were conducted Hg laboratory analysis. Laboratory works conducted at Intertek Jakarta using Fire Assay (FA) for Au grade, Atomic Absorption Spectrophotometry (AAS) for Cu, Ag, Pb, As, Zn and Hg. Results of the analysis were variety wide range grade of Au, i.e. 0.266 – 76 ppm. The wide range grade of Cu is 42-1230 ppm, 30- >4000 ppm of Pb, 74->10,000 ppm of Zn, <1-34 ppm of Ag, <40-550 ppm of As, and <0.01-0.16 ppm, respectively.